Translating name labels in comics from English to Bahasa Malaysia / Chan Jin-Vei - Chan, Jin-Vei (2014)
This research aims mainly to identify and describe the strategies used in the translation of name labels in the Spider-Man comic series from English to Bahasa Malaysia. This study will also assess the quality of the translation of the name labels given to the characters in the comics. The identification of the translation strategies will be based on Mona Baker‟s (2011) list of strategies which are, translation by using a more general word, translation by using a less expressive word, translation by using loan words, translation by paraphrasing using related words, translation by paraphrasing using unrelated words, translation by omission and translation using cultural substitution. The assessment of the translation quality will be based on Juliane House‟s translation quality assessment model where the target text is compared to the source text to see if the meaning of words in the source text are retained, lost or enhanced in the target text. The results showed that the three most frequently used strategies for translation of name labels in comics based on the data of this study are translation by paraphrasing using related words, translation by omission of words and translation by using a less expressive word. It was also discovered after comparing the target text with the source text that most of the name labels have lost their original meaning in the target text and although some words had their meanings retained, the impact of these words felt in the source text has been reduced and only one example from the data was discovered to have gained a new level of meaning in comparison to its source text counterpart.